Solutions to improve the bidding of public investment projects at the project management board of agricultural and rural development projects in Cà Mau province - Huỳnh, Quốc Đỉnh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
According to Clause 12, Article 4 of the Law on Bidding No. 43/2013/QH13 dated November 26, 2013 of the National Assembly (hereinafter referred to as the Law on Bidding 2013) clearly states the content of bidding: Bidding is the process of selecting contractors to sign and perform contracts for the provision of consulting services, nonconsulting services, procurement of goods, construction and installation; select investors to sign and implement investment project contracts in the form of public-private partnerships, investment projects with land use on the basis of ensuring competition, fairness, transparency and economic efficiency. During the research process, we proposed a number of solutions to complete the bidding for public investment projects at the Project Management Board of Agriculture and Rural Development in Ca Mau province.